A docência no Instituto de Biologia da Universidade Federal de Uberlândia: percorrendo caminhos e encontrando representações - Brito, Talamira Taita Rodrigues (2006)
The research had intended to deepen the discussions about the teaching practice in the university, searching to understand as it comes structuring itself in front the new demands of the University and like it has been working and representing in the day-to-day of the teachers. This study had as goal to come to light the representation of the teaching practice of the teachers from the Biology Institute of Federal University of Uberlândia. The research also had intended: To investigate how these representations impact in the teaching practice of these teachers and, how these practices interfere in the dynamic of these representations. To reveal how happened its formation to the teaching practice; To delimit the activities understood as teaching practice for these professionals, and also their affinities with them, searching for singularities to the college teaching practice in the researched group. To do this, we have had in mind three questions: Who knows and where knows from? What and how knows? What knows about and with what kind of effects? The data were collected through of a questionnaire applied to all teachers of Institute and also through an interview made with eight teachers, inserted into four areas of academic unity which was already mentioned. The Social Representation was the theoretical / methodology referential selected to conduct the research and analysis of the data. The representation found among the teachers are diversified, impregnated of values and subjectivity, fruits of a historical construction, soaked of cultural, social and politics representation. We hope that this work contributes to discussions around of university, teaching practices, and formation of teachers to college teaching.